Biocatalytic Synthesis of Chiral N‐Functionalized Amino Acids. (21st September 2018) - Hyslop, Julia F.; Lovelock, Sarah L.; Sutton, Peter W.; Brown, Kristin K.; Watson, Allan J. B.; Roiban, Gheorghe‐Doru
Abstract: N‐Functionalized amino acids are important building blocks for the preparation of diverse bioactive molecules, including peptides. The development of sustainable manufacturing routes to chiral N‐alkylated amino acids remains a significant challenge in the pharmaceutical and fine‐chemical industries. Herein we report the discovery of a structurally diverse panel of biocatalysts which catalyze the asymmetric synthesis of N ‐alkyl amino acids through the reductive coupling of ketones and amines. Reactions have been performed on a gram scale to yield optically pure N ‐alkyl‐functionalized products in high yields.